STRATEGI PENGEMBANGAN KAWASAN WISATA ALAM PULISAN KABUPATEN MINAHASA UTARA - Renardi ., Ariowibowo; Tommy F. Lolowang; Leonardus R. Rengkung (Sam Ratulangi University, 2017)
This study aimed to describe the potential and opportunities of Tourism Region Pulisan, identify any weaknesses and threats, and define management strategies of Pulisan Coastal Region. This research used descriptive method to interpret the data. This research was conducted at the Village of Pulisan, East Likupang Sub-district, North Minahasa Regency, North Sulawesi Province which began in March to August 2016. The sampling technique used purposive sampling and used Theory of Tourism System. Respondents in this study is the government of North Minahasa Regency. The data used in this study are primary data and secondary data. This study uses a model of SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) factors predefined both from the view of experts as well as existing regulation. Then analyze the internal and external factors that are arranged in a matrix of IFAs (Internal Factor Analysis) and EFAS (External Factor Analysis). Research using SWOT analysis weights and scores are determined based on the analysis of data obtained from the respondents. The results showed that the tourism area is Pulisan Tourism Regions with high natural potential and much in demand by tourists. Although the location is not too wide but has many interesting attractions Tourism Region of Pulisan natural appeal to different types of travelers with different motivations. Development undertaken by the community with the coaching is done by the Department of Tourism and Culture of North Minahasa provide a change of design in terms of tourist facilities. Rearrangement taking into account the priority needs of tourists in the tourism area, this will greatly affect its development, so that tourists and travelers can feel the value of Marine Tourism Region at an affordable price. Growth strategies that are used to provide benefits for local residents. High tourist visits every weekend is expected to give local residents the ability to develop, it need guidance from relevant agencies to provide more targeted development.